Educational Management Information Model for Special Student for Executives in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2022)
The aims of the paper was to study and evaluate educational management information model for special student for executives in Thai supply chain. The samples are ten experts in the field of information system ,supply chain and s p e c i a l education. The data is analysed by means and standardized deviations. The research result shows that the model consists of five elements namely main components, Suppliers, Manufacturer, Customers, Consumers The assessment of model using Black-Box technique and the result shows the overall rating mean of 3.68 and standard deviation of 0.62, which means that the model is appropriate at the high level. The model can develop information system.